2005
DOI: 10.1007/s10620-005-2964-3
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural Hearing Loss in Patients with Inflammatory Bowel Disease: A Subclinical Extraintestinal Manifestation

Abstract: Isolated case reports in which symptomatic hearing loss develops suddenly during the course of inflammatory bowel disease (IBD) have been reported, but the presence of subclinical sensorineural hearing loss (SNHL) associated with IBD has been investigated in only two preliminary studies. In order to research this further, we aimed to investigate the presence of subclinical SNHL in IBD by comparison with a control group and to examine possible relations between the bowel disease parameters and hearing loss.Otos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…Immune mediated inner ear disease includes clinical conditions associated with rapidly progressive unilateral or bilateral forms of sensorineural hearing loss (SNHL), or even acute total deafness. [16][17][18] A systemic auto-immune disorder including IBD may present in onethird of the cases. 19 The clinical manifestation of the disease is most often bilateral and progressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune mediated inner ear disease includes clinical conditions associated with rapidly progressive unilateral or bilateral forms of sensorineural hearing loss (SNHL), or even acute total deafness. [16][17][18] A systemic auto-immune disorder including IBD may present in onethird of the cases. 19 The clinical manifestation of the disease is most often bilateral and progressive.…”
Section: Discussionmentioning
confidence: 99%
“…Akbayir N et al investigated 39 IBD patients using otoscopy, tympanometry, and pure tone audiometry. 17 It was demonstrated that a subclinical sensorineural hearing loss might be associated with UC and somewhat with CD affecting mainly the high frequencies. In the light of this finding the authors suggest that all IBD patients should be investigated with labyrinth functions.…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that the inner ear, like other extraintestinal sites involved in GS, could become the target of an immune mediated response. Likewise, a subclinical sensorineural hearing loss, affecting mainly the high frequencies, has been associated with irritable bowel syndrome 17 , a syndrome in which GS has been suggested as a possible pathogenic factor 18 . Tinnitus is a symptom of multifactorial origin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on probable manifestations of UC in the nervous system, although few have noted neuropathy, and other EIMs have been reported (1-4). To the best of our knowledge, there are no reports of neuropathy of the hypoglossal nerve occurring in association with UC, although some studies have that noted the occurrence of cranial nerve disorders, such as optic neuritis, and sensorineural hearing loss (1,(5)(6)(7)(8)(9)(10)(11). Furthermore, one study found that demyelinating diseases occur more frequently in patients with UC than in non-UC patients (12).…”
Section: Discussionmentioning
confidence: 99%